Rheological characterization of coloured oil-in-water food emulsions with lutein and phycocyanin added to the oil and aqueous phases - Sousa, Isabel (2010)
The use of natural colourings in food products presents nutritional advantages, and certain pigments are associated with functional properties, e.g. antioxidant effects. This can be very advantageous in food products with high fat contents like mayonnaises. The aim of this work was to study the effect of adding natural pigments, lutein and phycocyanin, to the water and oil phases, respectively, of oil-in-water pea protein-stabilized emulsions, beyond the desirable and expected development of a green colour. The emulsions were prepared with 3% (w/w) pea protein, 65% (w/w) vegetable oil, and varying concentrations of lutein and phycocyanin (0.25–1.25% w/w). Emulsions containing both pigments, in different proportions (total pigment concentration of 0.5%, w/w) were also prepared. Oscillatory and steady-state measurements, as well as droplet size distribution and textural profile tests, were performed. The addition of lutein to the disperse oil phase promoted a decrease of the emulsions’ rheological and textural parameters, while the addition of phycocyanin to the water (continuous) phase resulted in an increase of these properties. When using combinations of both pigments, an increase of the rheological and textural parameters with phycocyanin proportion was apparent, and a synergetic effect due to the presence of both pigments was found.